A-Si TFT Integrated Gate Driver Workable at −40°C Using Bootstrapped Carry Signal - Jiwen Yang; Congwei Liao; Kun Wang; Junjun An; Shuai Shen; Shengdong Zhang (IEEE Access, 2022)
A thin-film transistors (TFTs) integrated gate driver which can work well at low temperature down to $- 40\,\,^{°} \text{C}$ is proposed and demonstrated. The carry signal (CN) of the driver, being generated through the voltage bootstrapping approach using a CN-connected capacitor, is used to pre-charge the following stage of the driver. As the rising and falling time of CN is much shorter than that of the gate driving signal GN, the bootstrapping voltage is increased and voltage loss of the pre-charge transistor can be much reduced, to avoid the driver’s malfunction at low temperature. This structure further benefits maintaining the driving speed over long operation time at high temperature. On the other hand, the GN, instead of CN, is used to reset the gate driver to suppress the voltage feed-through effects. One single stage of the driver consists of 11 TFTs and 2 capacitors, driven by 4 clock signals with the duty ratio of 25%. An a-Si:H TFTs implemented single stage circuit of the driver occupies an area of 250 $μ \text{m}× 1099\,\,μ \text{m}$ . Measurements show that the output voltage magnitude can be maintained well when temperature varies from $- 40\,\,^{°} \text{C}$ to 80 °C. Moreover, the rising-time and falling-time increase of the output pulse are both less than $3~μ \text{s}$ after 240 hours of the accelerated high temperature aging operations.